Benefits of using the Khan Academy platform in teaching practice - Takatu, Deivison Shindi (Revista Hipótese, 2019)
The Khan Academy platform is a free educational resource that is available on the internet for the whole world. It has many resources and content, allowing students and teachers to explore and benefit from its use. In addition, it provides a homogeneous environment, making the teaching-learning process more interesting for students. With the concepts of inverted classroom and hybrid teaching, learners become more active in class, becoming protagonists of their own learning. Therefore, the insertion of this resource during the classes, potentiates the interactions and school results of those involved.